Electron-phonon interaction and superconductivity in the multiband superconductor β-Bi2Pd. (May 2017) - Saib, S.; Karaca, Ertuǧrul; Tütüncü, H.M.; Srivastava, G.P.
Abstract: We have investigated the structural, electronic, and vibrational properties of β -Bi2 Pd in the body-centered tetragonal CaC2 structure using a generalized gradient approximation of the density functional theory and the ab initio pseudopotential method. There are several electronic bands near the Fermi energy, with varying degrees of dispersive behaviour, which arise dominantly from Bi 6p orbitals and also from Bi 5d and Pd 5p orbitals. A critical assessment of the Eliashberg spectral function reveals that Bi-related vibrations couple strongly with the electrons at the multiband Fermi energy. By integrating the Eliashberg spectral function, the values of the average electron-phonon coupling and the logarithmic average frequency are determined to be 1.03 and 79.23 K, respectively. With these values, the Allen-Dynes formula suggests the BCS superconducting transition temperature of T c = 5.5 K, in excellent agreement with the recently presented experimental value of 5.4 K. Graphical abstract: Highlights: The electronic structure of β -Bi2 Pd is investigated by using ab initio pseudopotential method. Phonons and electron-phonon interaction in β -Bi2 Pd are studied using a linear response theory. Bi-related phonon modes couple more strongly with electrons. β -Bi2 Pd is a conventional phonon-mediated superconductor with strong electronphonon coupling parameter of 1.03. The calculated T c of 5.5 K is in excellent agreement with the recent experimental value of 5.4 K.